(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Innovative teaching is the process of effectively introducing new teaching strategies and methods into the classroom teaching. The purpose of introducing these new teaching strategies and methods is to improve academic outcomes and resolve the real problems to promote equitable learning. The researcher wanted to study the impact of 3,2,1 innovative teaching on learning among the students and assess the feedback of the students. The study revealed that the innovative teaching method was statistically highly significant (P<0.0001) in enhancing the learning, It showed that innovative teaching yields great results and outcome. The students expressed positive opinion for the innovative teaching and felt that the method improved insight, interaction and clarity of subject content.